(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article examines the national significance of the British Royal Family as one of the most enduring symbols of the United Kingdom. From a historical, cultural, and linguocultural perspective, the monarchy represents continuity, identity, and unity within British society. The study explores how the Royal Family functions not only as a political institution but also as a symbolic and cultural phenomenon embedded in national consciousness. Special attention is given to the monarchy’s role in shaping national identity, preserving traditions, and acting as a unifying force in a modern democratic state.